Composition variation of the essential oil from Ocimum basilicum L. cv. Genovese Gigante in response to Glomus intraradices and mild water stress at different stages of growth. (June 2020) - Mota, Iris; Sánchez-Sánchez, José; Pedro, Luis G.; Sousa, Maria João
Abstract : In this study, a factorial experiment was carried out to investigate the effect of AMF (arbuscular mycorrhizal fungi) and water stress on the quality of fresh plants (through the analysis of essential oil composition) and also on the morphological characteristics (in terms of biomass) of basil ( Ocimum basilicum L. cv. Genovese Gigante). The factors included an arbuscular mycorrhizal fungus inoculation ( Glomus intraradices ), irrigation level (mild water stress, 60% Field capacity) and the interaction of both AMF and water stress. In addition, the effects of harvesting at two different developmental stages were assessed with respect to the plants tolerance to abiotic stress and the quality of the fresh plant. The main essential oil (EO) constituents for this cultivar were eugenol, which varied between 7.1 and 50.8%, and linalool, 17.0–54.7%, in all the samples. The highest relative amount of eugenol (50.8%) was obtained during the vegetative stage in plants under water stress whereas samples from the control presented 16.2% for this compound. The samples which were significantly different from the control samples were the WS (water stress) samples from the vegetative stage. Additionally, this study suggests that AMF plants offset the adverse effect of water stress. In this context, and since the interaction of AMF and water stress did not significantly change the fresh plant quality, i.e. the essential oil profile in both stages of development, it is worthwhile considering this method of production. Finally, this experiment permitted an understanding of the stressor thresholds of the species used and also that, compensatory responses occur at different time scales, including between generations and also during development (developmental plasticity). Graphical abstract: Image 1 Highlights: Comprehensive metabolomic comparison of O. basilicum cv. Genovese gigante during two growth stages. Ontogeny-related mechanisms of tolerance may play a role in the adaptation of Genovese gigante cultivar to water stress. The chemical composition of water-stressed plants is different during the vegetative stage in contrast to the flowering stage. IAMF allows obtaining equally good quality fresh plant material as the control while using less water resources.